A STUDY OF DEVELOPMENT AND VALIDATION OF A METHOD FOR SIMULTANEOUS ESTIMATION OF LOBEGLITAZONE SULFATE AND GLIMEPIRIDE USING REVERSEDPHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY IN DOSAGE FORM AND CHARACTERIZATION OF DEGRADANTS USING LIQUID CHROMATOGRAPHY–MASS SPECTROMETRY - RAVI CH; KIRAN KUMAR K; KRISHNAVENI G (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: A novel, speedy, and accurate high-performance liquid chromatography approach has been established for quantitatively analyzing lobeglitazone sulfate and glimepiride. Methods: In this method, the drugs were separated using Inertsil Octadecylsilyl (ODS) 250 × 4.6 mm, 5 μm column with a flow rate of 1 mL/min. The buffer consists of 1 mL of formic acid, which is dissolved in 1 L Milli-Q water, and a mobile phase consisting of a 50:50 (v/v) mixture of 0.1% formic acid and acetonitrile. The 260 nm wavelength was used for detection. Results: Lobeglitazone sulfate concentrations ranging from 12.5 μg/mL to 75 μg/mL and glimepiride concentrations from 25 μg/mL to 150 μg/mL show good linearity in the suggested approach. The limit of detection and limit of quantification values were 0.3 μg/mL, 1.0 μg/mL and 0.15 μg/mL, 0.5 μg/mL for glimepiride and lobeglitazone sulfate, respectively. All the parameters of accuracy, specificity, and method precision were all within the acceptable limit. Conclusion: In the forced degradation studies, the degradation products were characterized by the use of liquid chromatography–mass spectrometry. The current method was found to be simple, economical, suitable, and validated according to the International Council for Harmonization guidelines.